Meta-Management System for GENI - Maltz, Dave; Ng, T. S. Eugene; Gogineni, Hemant; Yan, Hong; Zhang, Hui; Cai, Zheng (2007)
Management of the geographically distributed GENI facility is a complex problem. The current proposed management architecture envisions a GENI Management Core (GMC) that remotely manages a set of physical computing and network elements (GENI components). The GMC must support remote network management capabilities such as remote component diagnostic and reboot, network service migration, and network maintenance operations. These capabilities need to remain functional even when other software systems have failed. To realize these remote management and diagnostic capabilities, GENI requires a robust communication channel for management traffic that is independent of the operation and health of any other GENI services.